Role of Transthoracic Lung Ultrasonography in the Diagnosis of Pulmonary Embolism: A Systematic Review and Meta-Analysis. - Libing Jiang; Yuefeng Ma; Changwei Zhao; Weifeng Shen; Xia Feng; Yongan Xu; Mao Zhang (PLoS ONE, 2015)
Background Pulmonary embolism (PE) is a potentially life-threatening condition. Although computed tomography pulmonary angiography (CTPA) is the reference standard for diagnosis, its early diagnosis remains a challenge, and the concerns about the radiation exposures further limit the general use of CTPA. The primary aim of this meta-analysis was to evaluate the overall diagnostic accuracy of transthoracic lung ultrasound (TLS) in the diagnosis of PE. Methods PubMed, Web of science, OvidSP, ProQuest, EBSCO, Cochrane Library and Clinicaltrial.gov were searched systematically. The quality of included studies was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 tool. The sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR) and hierarchical summary receiver operating characteristic (HSROC) curves were used to examine the TS performance. The Bayes analysis was used to calculate the post-test probability of PE. Publication bias was assessed with Deeks funnel plot. Results The results indicated that the sensitivity, specificity, PLR and NLR were 0.85 (95% confidence interval (CI), 0.78 to 0.90), and 0.83 (95% CI, 0.73 to 0.90). And the DOR and HSROC were 28.82 (95% CI, 17.60 to 47.21), 0.91(95% CI, 0.88, 0.93). Conclusions The present meta-analysis suggested that transthoracic lung ultrasonography is helpful in diagnosing pulmonary embolism. Although the application of transthoracic lung ultrasound may change some patients' diagnostic processes, it is inappropriate to generally use transthoracic ultrasonography in diagnosing pulmonary embolism currently.